2014
DOI: 10.1063/1.4865081
|View full text |Cite
|
Sign up to set email alerts
|

Results of the 2013 UT modeling benchmark obtained with models implemented in CIVA

Abstract: For several years, the World Federation of NDE Centers, WFNDEC, proposes benchmark studies in which simulated results (in either ultrasonic, X-rays or eddy current NDT configurations) obtained with various models are compared to experiments. This year the proposed UT benchmark concerns inspection configurations with multi-skips echoes. This technique is commonly used to inspect thin specimen and/or in case of limited access inspection. This technique relies on the use of T45° mode in order to avoid mode conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The set-up is more than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a. The numerical experiments conducted with CIVA [22] (a commercial package for analyzing and simulating NDT [23][24][25][26][27][28], in particular, NDT of components with irregular surfaces [7,8,28,29]) showed that the notch fabricated for the purposes of this experiment was best imaged using the half-skip LTT mode, with the L (longitudinal) transmitted signal converting at the backwall to the T (transverse) and then reflecting from the notch, so that the received signal is also T, see Figure 16a. The set-up is more challenging than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a.…”
Section: Testing Autonde On Cea Datamentioning
confidence: 99%
“…The set-up is more than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a. The numerical experiments conducted with CIVA [22] (a commercial package for analyzing and simulating NDT [23][24][25][26][27][28], in particular, NDT of components with irregular surfaces [7,8,28,29]) showed that the notch fabricated for the purposes of this experiment was best imaged using the half-skip LTT mode, with the L (longitudinal) transmitted signal converting at the backwall to the T (transverse) and then reflecting from the notch, so that the received signal is also T, see Figure 16a. The set-up is more challenging than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a.…”
Section: Testing Autonde On Cea Datamentioning
confidence: 99%
“…To validate the accuracy of the new parallel model, the results of both of its implementations have been studied. As the CIVA 11.0 software is validated against real experiments through benchmarking, especially during the QNDE 2013 conference, its simulations will serve as a point of reference for result validation [7].…”
Section: Results Validationsmentioning
confidence: 99%
“…The number of mesh points of the rough surface along the local axes x and y has then to be automatically fixed by the chosen mesh algorithm. The previously described Gaussian rough surface model is currently implemented for planar and cylindrical surfaces in 3D computations, and for their linear cross-sections in 2D, in the CIVA software [28] (platform for non-destructive evaluation simulation [29][30][31][32][33]). Examples of generated surfaces for small specimens with relatively high roughness are shown in Figure 1.…”
Section: Implementation Example For Generation Of An Individual Gaussian Rough Surfacementioning
confidence: 99%